Understorey Bird Communities 8 and 18 Years after River Diversion in Kihansi Gorge, Udzungwa Mountains in the Eastern Arc Mountains, Tanzania - Werema, Chacha; Msuya, Charles A. (Tanzania Journal of Science, 2019)
On the most south-western slopes of the Udzungwa Mountains in Tanzania lies Kihansi River. The river was diverted underground in 2000 to run electric turbines for electricity generation. Using mist netting, pre-diversion (in 1998 and 1999) and short term post-diversion (in 2001) effects of the river diversion on understorey birds were undertaken before and year after river diversion, respectively. Intermediate and long-term effects of river diversion on understorey birds at the same transects are non-existent. In September 2008 and August and September 2018, using mist nets, birds were surveyed at the same transects to assess whether or not there have been changes in avian community structure, abundance and diversity eight and 18 years after the river was diverted. Results suggest that there have been no significant changes in pre- diversion and eight and 18 years post-diversion birds’ species abundances and diversities. This suggests that the diversion of the river has had no intermediate term effects on avifauna in the gorge. Keywords: Avian community composition, Kihansi River, Mist netting, River diversion, Species diversity, Understorey forest birds